Implementation of Adab Assembly in Student Character Development at Sttd Al – Busyro Surakarta - Kharisma Aulia Dianitha; Ahmad Agung Yuwono (Journal of Social Research, 2024)
Elementary level Tahfizhul Qur'an school which emphasizes learning on tahfizhul Qur'an (memorizing the Al-Qur'an) and applying adab before knowledge. The aim of this research is to find out the implementation of etiquette at STTD Al Busyro. This research uses a qualitative research approach with the type of field research. Data collection methods through interviews, observation and documentation. The data analysis method used in the research is by using the Miles and Huberman model, namely data reduction, data presentation and drawing conclusions. The results of this research are the Concept of Applicable Religious Adab Education. The ethical values ??that are emphasized and prioritized at STTD Al Busyro are divided into three aspects, namely; Judging from the pattern of attitudes and behavior towards Allah such as praying and worshiping, behavior towards humans such as helping each other, and behavior towards nature or the universe such as protecting nature. There are several stages that are carried out in order to get maximum results in implementing adab, namely the socialization, implementation and evaluation stages.